Interaction of myricetin, ampelopsin (dihydromyricetin), and their sulfate metabolites with serum albumin, cytochrome P450 (CYP2C9, 2C19, and 3A4) enzymes, and organic anion‐transporting polypeptides (OATP1B1 and OATP2B1) - Ágnes Dombi; Hana Kaci; Kateřina Valentová; Éva Bakos; Csilla Özvegy‐Laczka; Miklós Poór (Wiley, 2024)
Abstract Myricetin (MYR) and ampelopsin (AMP, or dihydromyricetin) are flavonoid aglycones found in certain plants and dietary supplements. During the presystemic biotransformation of flavonoids, mainly sulfate and glucuronide derivatives are produced, which are the dominant metabolites in the circulation. In this study, we tested the interactions of MYR, myricetin‐3'‐O‐sulfate (M3'S), AMP, and ampelopsin‐4'‐O‐sulfate (A4'S) with human serum albumin (HSA), cytochrome P450 enzymes (CYPs), and organic anion‐transporting polypeptides (OATPs) using in vitro models, including the recently developed method for measuring flavonoid levels in living cells. M3'S and MYR bound to albumin with high affinity, and they showed moderate displacing effects versus the Site I marker warfarin. MYR, M3'S, AMP, and A4'S exerted no or only minor inhibitory effects on CYP2C9, CYP2C19, and CYP3A4 enzymes. M3'S and MYR caused considerable inhibitory actions on OATP1B1 at low micromolar concentrations (IC50 = 1.7 and 6.4 μM, respectively), while even their nanomolar levels resulted in strong inhibitory effects on OATP2B1 (IC50 = 0.3 and 0.4 μM, respectively). In addition, M3'S proved to be a substrate of OATP1B1 and OATP2B1. These results suggest that MYR‐containing dietary supplements may affect the OATP‐mediated transport of certain drugs, and OATPs are involved in the tissue uptake of M3'S.